Selayang Hospital Project - Chor, Choy Yook (1999)

(untitled)
The planning of Selayang Hospital started in 1996, a proposed 960-bedded hospital located on a 15.8 hectare site along the Kepong Selayang road, within the Majlis Perbandaran of Selayang of Gombak District in the state of Selangor. Selayang Hospital (SH) is a government - owned ultra - modern hospital in the country. It has sophistication of a luxury private medical center with state - of - the -art technology. It is one of the hospitals built under the Seventh Malaysia Plan (7th MP) to reduce congestion at the Kuala Lumpur Hospital (KLH). Health Minister Dato' Chua lui Meng, (Viswanathan, 1998), said that the reasons for building this 960-bedded hospital is because the Ministry of Health (MOH) had for a longtime realized that the KLH was too much overcrowded with patients. Physically the KLH was already bursting to its limits with staff overworked, quality of patient care compromised and as a result patient's dissatisfaction and complaints. Proper documentation on archives was not available with many patients' records mislaid or missing. This had resulted on many lost cases for the KLH in legal matters. It was with the above background that the MOH came up with SHP, with its modern IT setting.